ADAPTATION TO CLIMATE CHANGE IN CULTIVATION OF RESIDENTS IN DALAT CITY, LAMDONG PROVINCE: CASE STUDY IN WARD 7 - Phạm Hồng Hải (Tạp chí Khoa học Đại học Đà Lạt)
Climate change has been one of the greatest challenges for humanity. Climate change affects most sectors of the economy, from agriculture, forestry, fisheries to oil and gas, hydropower and shipping. Crop production is one of the sectors of the economy affected directly and severely by climate change. This paper contributes to an initial assessment of some of the manifestations of climate change in Dalat city and its impact on crop production in the area of Ward 7, as well as how households respond to climate change. On that basis, we recommend some measures to improve the capacity of households to adapt to climate change in farming.